Solve the equatio
To find: Roots of the equation
To solve the quadratic equation by factorisation method, follow the steps:
1) Multiply the coefficient of x2 and constant term.
2) factorise the result obtained in step 1.
3) Now choose the pair of factors in such a way that after adding or subtracting(splitting) them
You get coefficient of x.
⇒ 2ab (2x – 2a – b – 2x) = (2a + b)2x (2a + b + 2x)
⇒ 2ab (-2a – b) = 2(2a+ b) (2ax + bx + 2x2)
⇒ -ab = 2ax + bx + 2x2
⇒ 2x2 + 2ax + bx + ab = 0
⇒ 2x (x + a) + b (x + a) = 0
⇒ (2x + b) (x + a) = 0
Hence the roots are .
Rate this question :